La representación social de los migrantes venezolanos en el diario la Hora - García, Holger (2020)
This present case study allows us to identify what social representation Venezuelan emigrants have in Ecuadorian territory, the employment situation they represent and what reception they represent in Ecuador, this is done through qualitative research, since it allows us to study the behavior of a individual or a population. The results obtained can be used at the time of requesting a workforce from Venezuelan emigrants.